RESEARCH STATUS AND PROSPECTS OF SHARIAH COMPLIANCE IMPACT ON FIRM RISK, PERFORMANCE AND RESILIENCE - Touti, Nihal; Alaoui Taïb, Asmâa (Bank Indonesia, 2024)
This article performs a bibliometric analysis on the impacts of Shariah compliance on firms’ risk, performance, and resilience. Using Scopus database, a total of 1063 documents have been identified and analyzed utilizing VOSviewer. In the analysis, we evaluate co-authorship, keyword co-occurrence, and citation to identify influential authors, countries, and sources. The findings reveal a consistent increase in publications, particularly noticeable from 2014 onwards, indicating a growing interest in this research domain. Notably, the study highlights the pivotal role of Shariah compliance in enhancing corporate governance, financial risk management, and sustainable development, thus directly impacting the risk, performance, and resilience of firms. Globally it seems that by adhering to Shariah principles, firms can mitigate risks effectively, enhance their performance, and strengthen their capacity to withstand market fluctuations and economic uncertainties, thereby improving their overall resilience. These findings underscore the global significance of Shariah-compliant finance and emphasize the imperative for further research to deepen the understanding of its implications for firms.